The effectiveness of the buddy support system on teacher-parent collaboration and students’ social interaction in special education in Malaysia / Donnie Adams Paramasivam - Donnie Adams, Paramasivam (2016)

(untitled)
This research examined the effectiveness of the buddy support system on teacher parent collaboration and students’ social interaction in special education in Malaysia. Until recently, there has been growing awareness of the powerful influence a peer group can have in supporting inclusion. The study will explore teachers’ and parents’ understanding of special educational practices, their willingness to communicate with each other, their perceived roles as well as their expectations of each other in which these elements were deemed vital in a collaboration process that encourages students’ social interaction while the effectiveness of the Buddy Support System as a moderator is investigated in this collaboration process. This study adopted a sequential mixed method design, where quantitative data was collected using teachers’ and parents’ questionnaires which highlights the elements and importance of collaboration for a successful special education programme, the elements of friendship, interactions, acceptance by classmates, the importance of social interaction of young students with special needs, and the elements of the effectiveness of the buddy support system. Two types of statistical techniques were used to analyze the quantitative data. Descriptive statistics comprising mean and standard deviation were used to analyze data relating to the domains of teacher-parent collaboration, students’ social interaction among SEN and mainstream pupils and the effectiveness of the buddy support system as perceived by teachers and parents. Inferential statistics comprising Pearson's R Correlation was used to analyze the relationship between teacher-parent collaboration and students’ social interaction as perceived by the teachers and parents. PROCESS procedure for SPSS (Hayes, 2013) was used to determine whether the buddy support system significantly moderates the relationship between teacher-parent collaboration and students’ social interaction in the implementation of special educational practices. Results showed that the teachers rated   iv  themselves highest on the understanding about SEN while parents rated themselves highest on the expectations of teachers’ role in the implementation of SEN. Both teachers and parents rated the acceptance by classmates domain the highest in students’ social interaction among SEN and mainstream pupils. Teachers rated the influence and benefit domain of the buddy support system the highest while parents rated highest on the influence domain of the buddy support system. Hierarchical multiple linear regression results were able to confirm that by controlling the Buddy Support System variables (moderators), teacher-parent collaboration domain did not significantly predict the students’ social interaction domains, which accounted for a significant proportion of the variance in students’ social interaction. Emerging themes from the qualitative data supports the quantitative data results. The findings of this study will provide essential guidelines for fostering effective buddy support system on teacher-parent collaboration in special educational practices. Training and support could be further provided by MOE to aid the goal towards 75% of students with special needs enrolled in inclusive programs by 2025.